Exploring The Influence Of Vitamin D In The Management Of Acne Vulgaris: A Pilot Study - Naheed, Aqsa; Mughal, Aashi; Zehra, Tehzeeb; Aamir, Rahila; Fida, Samina; Naveed, Taha (Journal of Rawalpindi Medical College, 2023)
Objective: The study aimed to explore the potential benefits of vitamin D supplementation in improving acne severity. Methods: This pilot study was carried out at HIT Hospital, Taxila. The study included nine female patients aged between 12 and 30 years, with acne vulgaris and having deficient serum 25-hydroxyvitamin D3 (25(OH)D) levels (<30 nmol/L). Exclusion criteria included the use of topical or oral treatments for acne, including retinoids, as well as those with a history of multivitamin or systemic steroid intake, and patients with any chronic disease. Global Acne Grading (GAG) score was used to assess the severity of acne vulgaris. Patients received a daily dosage of 1000 IU of vitamin D drops per day for 2 months so that vitamin D deficiency is corrected. After 2 months, the GAG score was re-calculated and documented. Data analysis was performed using SPSS version 28. Results: The mean age of the study participants was 18.33 years (SD= 3.3 Years). A statistically insignificant association (p=0.49) and weak positive correlation (r= 0.17, p=0.65) were observed between Vit D levels and acne Status and GAG-1 score on applying chi-square test and Pearson correlation respectively. A paired-sample t-test showed a significant difference in the GAG-1 Score (Mean=25.44, SD=7.6) and GAG-2 Score (M=15.1, SD=4.5) after Vit D supplementation. t (5.3), (p= 0.001). Conclusion: The results suggest that correcting vitamin D deficiency through supplementation resulted in a significant improvement in acne severity. Keywords: Acne vulgaris, Vitamin D, GAG score